KESEPIAN, KECERDASAN SOSIAL DAN HARGA DIRI PADA REMAJA DI MASA PANDEMI COVID-19 - Tanzil, Abigail Theodora; Satiadarma, Monty P; Roswiyani, Roswiyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
ABSTRACT The COVID-19 pandemic has affected almost every aspect of life, including people's daily activities, especially groups of children and adolescents due to the implementation of physical distancing, which also affects the social life of adolescents, where many activities are carried out online, include online learning. Due the pandemic, adolescents cannot socialize normally, and makes them feel a social shackles and feel alone. This study aims to see the effect of self-esteem on the relationship between social intelligence and loneliness in adolescents during online learning in Covid-19 pandemic. This research is a non-experimental descriptive quantitative research. Participants in this study were adolescents in Indonesia, age 15-21 years old, 68 participants. The measuring instruments used in this study were the UCLA Loneliness scale Version 3, the Tromso Social Intelligence Scale, and the Modified Rosenberg Self Esteem scale. This study uses correlation analysis and linear regression analysis. The results showed that there was a relationship between social intelligence and loneliness sig <0.01, then in the regression test, the results showed p = 0.245> 0.05, which means that self-esteem did not affect the relationship between social intelligence and loneliness. In this study, it was found that research participants had high scores of loneliness, but also high scores of social intelligence and high scores of self-esteem. this could happen because they experience distance separation from their social environment which makes participants feel lonely, feel alone, bored, feel that their social relationships are not as expected which is then perceived as lonely.Keywords: Adolescents, Loneliness, Self-Esteem, Social Intelligence ABSTRAKPandemi COVID-19 telah mempengaruhi hampir semua aspek kehidupan, termasuk aktivitas sehari-hari masyarakat, terutama kelompok anak-anak dan remaja akibat penerapan physical distancing, yang juga berdampak pada kehidupan sosial remaja, dimana banyak aktivitas dilakukan ...